Analysis Of The Influence Of Work Environment And Learning Culture On Employees' Work Commitment In National Airline Company Garuda Indonesia - Murad, Anizir Ali; Aminah Lubis; Wulandari; Ani Rakhmanita; Musran Munizu (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
The purpose of this study is to examine how organizational learning and work environment affect commitment to the company. Both quantitative and descriptive research methodologies are used in the study. Researchers employed descriptive research in this study. Non-probability sampling was employed in this study, and the sample size was one hundred participants. The author of this study collected data from respondents via questionnaires, interviews, and observation. Multiple regression analyses have been used in this study. The organizational commitment variable is positively and significantly impacted by the independent variables organizational learning and work environment, according to the results of the individual parameter significance test. These findings suggest that factors related to the work environment and effective organizational learning can raise the degree of organizational commitment. The study's findings also demonstrate that organizational dedication is positively impacted by the workplace. Overall, the study's findings point to the need for businesses to focus on and enhance organizational learning in the workplace because doing so can increase workers' organizational commitment. Emphasis on adequate facilities, good learning opportunities, leader support, a comfortable work environment, and interaction between employees can help increase the level of organizational commitment within the company.